Contribution of the MP2RAGE 7T Sequence in MS Lesions of the Cervical Spinal Cord - Testud, B.; Fabiani, N.; Demortière, S.; Mchinda, S.; Medina, N.L.; Pelletier, J.; Guye, M.; Audoin, B.; Stellmann, J.P.; Callot, V. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: The detection of spinal cord lesions in patients with MS is challenging. Recently, the 3D MP2RAGE sequence demonstrated its usefulness at 3T. Benefiting from the high spatial resolution provided by ultra-high-field MR imaging systems, we aimed to evaluate the contribution of the 3D MP2RAGE sequence acquired at 7T for the detection of MS lesions in the cervical spine.MATERIALS AND METHODS: Seventeen patients with MS participated in this study. They were examined at both 3T and 7T. The MR imaging examination included a Magnetic Imaging in MS (MAGNIMS) protocol with an axial T2*-WI gradient recalled-echo sequence (“optimized MAGNIMS protocol”) and a 0.9-mm isotropic 3D MP2RAGE sequence at 3T, as well as a 0.7-mm isotropic and 0.3-mm in-plane-resolution anisotropic 3D MP2RAGE sequences at 7T. Each data set was read by a consensus of radiologists, neurologists, and neuroscientists. The number of lesions and their topography, as well as the visibility of the lesions from one set to another, were carefully analyzed.RESULTS: A total of 55 lesions were detected. The absolute number of visible lesions differed among the 4 sequences (linear mixed effect ANOVA, P = .020). The highest detection was observed for the two 7T sequences with 51 lesions each (92.7% of the total). The optimized 3T MAGNIMS protocol and the 3T MP2RAGE isotropic sequence detected 41 (74.5%) and 35 lesions (63.6%), respectively.CONCLUSIONS: The 7T MP2RAGE sequences detected more lesions than the 3T sets. Isotropic and anisotropic acquisitions performed comparably. Ultra-high-resolution sequences obtained at 7T improve the identification and delineation of lesions of the cervical spinal cord in MS.GREgradient recalled-echoLMElinear mixed effectMAGNIMSMagnetic Resonance Imaging in MSUNIuniform